2009
DOI: 10.1038/ng.452
|View full text |Cite
|
Sign up to set email alerts
|

Multiple loci on 8q24 associated with prostate cancer susceptibility

Abstract: Previous studies have identified multiple loci on 8q24 associated with prostate cancer risk. We performed a comprehensive analysis of SNP associations across 8q24 by genotyping tag SNPs in 5,504 prostate cancer cases and 5,834 controls. We confirmed associations at three previously reported loci and identified additional loci in two other linkage disequilibrium blocks (rs1006908: per-allele OR = 0.87, P = 7.9 x 10(-8); rs620861: OR = 0.90, P = 4.8 x 10(-8)). Eight SNPs in five linkage disequilibrium blocks wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
238
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(249 citation statements)
references
References 15 publications
9
238
2
Order By: Relevance
“…[4][5][6] PCa is one of the common cancers with a large genetic component, as up to 42% of the risk could be explained by inheritance from studies about twins. 7 Genome-wide association studies (GWAs) have identified 46 susceptibility loci associated with PCa [8][9][10][11][12][13][14][15][16][17][18][19][20] that individually contribute to a small increase in PCa risk, but which taken together, could explain more than 25% of the excess of PCa familial risk. 13 Although present in only 1%-2% of sporadic PCa cases [21][22][23] germline mutations in the breast cancer predisposition gene 2 (BRCA2) are the genetic events known to date that confer the highest risk of PCa (8.6-fold in men f65 years).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] PCa is one of the common cancers with a large genetic component, as up to 42% of the risk could be explained by inheritance from studies about twins. 7 Genome-wide association studies (GWAs) have identified 46 susceptibility loci associated with PCa [8][9][10][11][12][13][14][15][16][17][18][19][20] that individually contribute to a small increase in PCa risk, but which taken together, could explain more than 25% of the excess of PCa familial risk. 13 Although present in only 1%-2% of sporadic PCa cases [21][22][23] germline mutations in the breast cancer predisposition gene 2 (BRCA2) are the genetic events known to date that confer the highest risk of PCa (8.6-fold in men f65 years).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive epigenetic mapping analysis has identified several enhancer elements within the risk loci that show tissue-specific activity both in vitro and in vivo (22,23). Apart from the rs6983267, another regulatory SNP has been identified in the enhancers, namely rs11986220, which is strongly correlated with prostate cancer predisposition SNP rs10090154 (2). It affects a FoxA1 binding site within an androgen-responsive enhancer at PrCa-1 region (22).…”
Section: Normal Functions Of the Regulatory Elements At 8q24mentioning
confidence: 99%
“…1). For example, multiple independent risk loci for prostate cancer are located at 8q24 (2)(3)(4)(5)(6), and predisposition alleles to several other epithelial cancers are also found in distinct linkage disequilibrium blocks within this region. An intriguing aspect of the risk alleles is that they are located in a 1.2-Mb "gene desert" region.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] This 7.5-Mb locus overlaps with the 8q24 region, which has been reported in linkage and GWASs of PrCa 17,23,24,29,32 and has been replicated in many studied populations. 22,25,26,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] The prostate stem cell antigen maps to this region 69 as does the oncogene MYC. The region has been extensively studied and is relatively gene-poor.…”
Section: Discussionmentioning
confidence: 99%
“…17,[22][23][24][25][26][27][28][29][30][31][32] However, more work remains to be done to fully elucidate the role of heredity in the complex disease of PrCa. The causative genes responsible for these associations are still unknown.…”
Section: Introductionmentioning
confidence: 99%